Meritve dimenzij: Praktikum (navodila za vaje pri predmetu Inženirska orodja 1) - Črepinšek Lipuš, Lucija (University of Maribor Press, 2021)
Dimensional Measurements: Practicum (Instructions for Exercises in the Subject Engineering Tools 1). Dimension measurement practicum is a study tool for performing laboratory exercises in the subject Engineering Tools 1. Exercises are intended to learn simple techniques for measuring dimensions in manufacturing engineering. It includes the implementation of various examples of measurements with an emphasis on finding solutions to achieve the lowest possible errors and the best possible measurement reliability.